High latrine coverage is not reducing the prevalence of soil-transmitted helminthiasis in Hoa Binh province, Vietnam - Yajima, A.; Jouquet, Pascal; Trung, D.D.; Cam, T.D.T.; Cong, D.T.; Orange, Didier; Montresor A. (Oxford University Press, 2009)
A baseline epidemiological survey for parasite infections was conducted between December 2007 and January 2008 in 155 villagers in a rural commune in Hoa Binh province, Vietnam. The prevalence of Ascaris lumbricoides, Trichuris trichiura and hookworm infection was 13.5%, 45.2% and 58.1%, respectively. At least one of the parasites was detected in 72.3% of the samples. We found no association between infection with A. lumbricoides or T. trichiura and engagement in agriculture, while hookworm infection was more prevalent in populations having frequent contact with soil. Agricultural use of human faeces was not correlated with any of the infections. We suggest that the consumption of vegetables that are commonly fertilized with human faeces in the community has led to the high infection rates with A. lumbricoides and T. trichiura, rather than the manipulation of faeces in farming activity. This also explains the high infection prevalence, despite high latrine coverage (98.1%) in the study population. The presence of latrines alone is not sufficient to reduce the prevalence of helminthiasis in a rural agricultural community if fresh faeces are used as fertilizer.